Potential use of selected citrus rootstocks and interstocks against HLB disease in Malaysia. - Shokrollah, Hajivand; Abdullah, Thohirah Lee; Sijam, Kamaruzaman; Abdullah, Siti Nor Akmar (Elsevier BV, 2011)
Huanglongbing (HLB), also known as citrus greening disease, has spread to and is seriously threatening the citrus industry in more than 40 countries. The HLB pathogen is a phloem limited bacteria, Candidatus Liberibacter spp. There is little information pertaining to the effects of different citrus rootstocks and interstocks against HLB in Citrus reticulata. The objective of this study was to evaluate the beneficial effects of different combinations of citrus rootstocks and interstocks against HLB using side grafting. There were no symptoms of HLB when C. grandis was used as rootstock with C. hystrix as the interstock and vice versa six months after inoculation. However, C. Liberbribacter asiaticus was detected in the scion using second PCR amplification. A high rate of disease severity was observed when C. aurantum was used as rootstock and C. aurantifolia as the interstock and vice versa. This study showed that C. Liberibacter asiaticus can be detected by conventional PCR and characteristics of their detrimental effects include low rate of vegetative growth and reduction of dry matter, root dry matter, plant height and stem diameter.